2008
DOI: 10.1177/0891988707311563
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression and Disability in Older Primary Care Patients With Heart Failure

Abstract: The purpose of this study was to examine the association between dependence in activities of daily living (ADL) and instrumental ADL (IADL) and major depression among 415 community-dwelling primary care patients age 65+ with heart failure and significant ADL or IADL dependence. Main findings include (1) a progressive increase in depression prevalence from 0% for no IADL dependence to about 40% for 6 IADL dependencies (P < .001), (2) a steady rise in depression prevalence to 40% for 6 ADL dependencies following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 42 publications
1
22
0
1
Order By: Relevance
“…This is perhaps not surprising given that instrumental ADLs consists of tasks important for self-care maintenance such as medication management. For instance, poor adherence to treatment recommendations (e.g., medication regimens) in HF has been linked with recurrent hospital readmissions, mortality risk, and worsening HF symptoms [7,34,35]. Interestingly, the rate of impairment in simple tasks such as telephone use nearly quadrupled at the 12-month follow-up in this study, suggesting HF patients may be at significant risk for inability to perform critical self-monitoring and life-saving behaviors (e.g., calling 9-1-1 or making doctor appointments).…”
Section: Discussionmentioning
confidence: 99%
“…This is perhaps not surprising given that instrumental ADLs consists of tasks important for self-care maintenance such as medication management. For instance, poor adherence to treatment recommendations (e.g., medication regimens) in HF has been linked with recurrent hospital readmissions, mortality risk, and worsening HF symptoms [7,34,35]. Interestingly, the rate of impairment in simple tasks such as telephone use nearly quadrupled at the 12-month follow-up in this study, suggesting HF patients may be at significant risk for inability to perform critical self-monitoring and life-saving behaviors (e.g., calling 9-1-1 or making doctor appointments).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown a relationship between cardiac dysfunction and limited physical capacity, depression and cognitive impairment [4][5][6][7][8]. However, little is known about this relationship in the very elderly.…”
Section: Introductionmentioning
confidence: 96%
“…2 Prior work has demonstrated that among persons with heart failure older persons are more likely than younger persons to be disabled, 3 but relatively little is known about the risk factors for developing disability among older persons with heart failure. 4–6 The burden of disability in an aging society is one of the most pressing problems facing our healthcare system today. Onset of disability can lead to loss of independence, the need for hospital and long-term nursing-home care, and premature death.…”
Section: Introductionmentioning
confidence: 99%